Impact Of Income On Consumption Behavior Of Urban Muslim Community In Kediri City (Case Study at Bandar Kidul Village Kecamatan Mojoroto Kediri) - Siti Nur Mahmudah; Tika Widiastuti; Achsania Hendratmi (Universitas Muhammadiyah Prof Dr Hamka, 2018)
The income of the Muslim community in the village of Bandar Kidul Kecamatan Mojoroto Kediri is mostly a woven cloth businessman who became the livelihood for the Muslim community in Bandar Bandar Kidul. This effort has been fostered by Bank Indonesia which is the Central Bank which is very supportive of this ikat business. Most of the Muslim community's income in Bandar Bandar Kidul comes from ikat business. When the ikat orders surged high, the income of the community will also increase and affect the consumption behavior of the Muslim community in the village of Bandar Kidul Kecamatan Mojoroto Kediri. This research uses the descriptive qualitative method with case study research strategy. Methods of data collection using interview method. Interviews were conducted with eight informants, namely ikat weaving businessmen and caretakers of pesantren huts. Based on the results of the study, the researcher can conclude that income has a very big impact on consumption behavior of urban Muslim community in the village of Bandar Kidul Kecamatan Mojoroto Kediri with some indicators namely; The first indicator with the amount of expenditure, the second indicator with the indicator of Islamic consumption, and the third indicator is the indicator of need fulfillment. Of the three indicators above can be seen that income has a positive impact on the consumption behavior of urban Muslim communities in the village of Bandar Kidul Kecamatan Mojoroto Kediri. This is evidenced by the amount of expenditure that is adjusted to the income, pay attention to the goods consumed for halal and thayyib and not extravagant and exaggerated, the fulfillment of income-adjusted needs.